Aluminium chloride-induced hippocampal damage: CA3 hippocampal subfield involvement and the neuroprotective role of Buchholzia coriacea ethanolic seed extract - Stephen Taiye Adelodun; Oluwadamilola Adunni Ishola; Ayodeji Zabdiel Abijo; Sunday Yinka Olatunji; Joshua Oladele Owolabi; John Afees Olanrewaju; Damilare Adedayo Adekomi (Phytomedicine Plus, 2021)
ABSTRACT: Background: Early signs of neurodegenerative events of Alzheimer's disease manifest within the hippocampus and presents as cognitive and memory impairment. Aluminium-chloride (AlCl3), a neurotoxicant interferes with the structure and functions of the hippocampus as well as its neurogenesis, thereby causing cognitive and memory impairment. Buchholzia coriacea (BC), a plant of nutraceutical value is traditionally reputed to boost memory and cognitive functions. This study elucidated the neuroprotective role of Buchholzia coriacea seed extract on AlCl3-induced hippocampal neuronal damage in Wistar rat model by examining the biochemical, histological, immunohistochemical, and neurobehavioural changes. Methods: Twenty-five male Wistar rats were randomly assigned into five groups A-E (n = 5). Group A served as the control, groups B-E were given 200 mg/kg of AlCl3 for 14 days and then received 2 mLs/kg distilled water, 50mg/kg BC, 100mg/kg BC and 2.5mg/kg donepezil respectively for 14 days orally. Glutathione and neurotransmitters (Glutamate, dopamine, and acetylcholine) levels, G6PDH and neurobehavioral activities, as well as histological (H and E, LFB and Cresyl violet stains) and immunohistochemical (ionized calcium-binding adapter molecule 1, Iba-1) changes were evaluated Results: AlCl3 impaired spatial working memory with observable improvements in the treated groups. Enzymatic activity and neurotransmitter levels were augmented in the group treated with the highest dose of BC compared to the control. Histological assessment showed that BC high-dose mitigated neurodegenerative changes in the CA3 hippocampal subfield. Conclusion: Taken together, BC exhibited neuroprotective ability on AlCl3-induced CA3 hippocampal field neuronal damage and demonstrated memory impairment reversing ability.